2020
DOI: 10.1111/bju.14997
|View full text |Cite
|
Sign up to set email alerts
|

Split renal function in patients with renal masses: utility of parenchymal volume analysis vs nuclear renal scans

Abstract: ConclusionPVA has utility for estimation of SRF in patients with renal masses, even though this population is older and more comorbid than renal donors and the tumour can complicate the analysis. PVA can be obtained by software analysis from preoperative cross-sectional imaging and thus readily incorporated into routine clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Now such measurements are facilitated by readily available software that provides highly accurate estimates of tumour and parenchymal volumes. Incorporation of direct measurements of vascularized parenchymal volumes into the analyses confirmed the results of the initial studies, and the relationship between parenchymal volume saved and function saved after PN was even stronger, nearly 1–1, reflecting more accurate estimation of the input parameters [22–26].…”
Section: New Perspectives On Ischaemia: the Importance Of Parenchymal...mentioning
confidence: 71%
“…Now such measurements are facilitated by readily available software that provides highly accurate estimates of tumour and parenchymal volumes. Incorporation of direct measurements of vascularized parenchymal volumes into the analyses confirmed the results of the initial studies, and the relationship between parenchymal volume saved and function saved after PN was even stronger, nearly 1–1, reflecting more accurate estimation of the input parameters [22–26].…”
Section: New Perspectives On Ischaemia: the Importance Of Parenchymal...mentioning
confidence: 71%
“…For instance, large and likely aggressive tumors tend to compromise a greater amount of healthy renal parenchyma, resulting in decreased split renal function of the ipsilateral kidney in comparison with the contralateral kidney, as evidenced in several studies from our group and others. 19–21…”
Section: Discussionmentioning
confidence: 99%
“…The greater the loss of renal parenchyma, the more severe the loss of renal function 10 . Ye et al 11 . showed that renal PV analysis may be of great practical value in estimating renal mitotic function, thus eliminating the need for nuclear renal scanning.…”
Section: Discussionmentioning
confidence: 99%